Therapeutic Strategies for Diabetes: Immune Modulation in Pancreatic β Cells - Jo, Sugyeong; Fang, Sungsoon (Frontiers in Endocrinology, 2021)
Increased incidence of type I and type II diabetes has been prevailed worldwide. Though the pathogenesis of molecular mechanisms remains still unclear, there are solid evidence that disturbed immune homeostasis leads to pancreatic β cell failure. Currently, autoimmunity and uncontrolled inflammatory signaling pathways have been considered the major factor in the pathogenesis of diabetes. Many components of immune system have been reported to implicate pancreatic β cell failure, including helper T cells, cytotoxic T cells, regulatory T cells and gut microbiota. Immune modulation of those components using small molecules and antibodies, and fecal microbiota transplantation are undergoing in many clinical trials for the treatment of type I and type II diabetes. In this review we will discuss the basis of molecular pathogenesis focusing on the disturbed immune homeostasis in type I and type II diabetes, leading to pancreatic β cell destruction. Finally, we will introduce current therapeutic strategies and clinical trials by modulation of immune system for the treatment of type I and type II diabetes patients.